Pengaruh Discovery Inqury Dengan Tinjauan Rraktek Dan Teoritis Pada Materi Getaran Terhadap Kemampuan Berfikir Kritis - Supriyadin, Dedi (Universitas Nggusuwaru, 2024)
This study aims to determine the effect of Discovery Inquiry Learning with practical and theoretical reviews, accompanied by animations, on critical thinking skills in the topic of vibrations and waves during the even semester of the 2016/2017 academic year. The research sample consisted of 58 students, divided into 29 students in the experimental group and 29 students in the control group. The research design used was the Posttest Control Group Design, and the analysis method applied was two-way analysis of variance (ANOVA). The results of the study showed that: (1) There was no difference in students' understanding of critical thinking between those who used the Discovery Inquiry learning model and those who followed conventional learning methods. In the Discovery Inquiry learning model, the significance value obtained was 0.117, which was smaller than the significance threshold (i.e., sig < 0.05). Meanwhile, in the Conventional learning model, the significance value obtained was 0.01, which was considered small because it was below the significance threshold (sig > 0.01).